Avaliação da glicemia basal como marcadora de morbidade no escorpionismo infantil - Tatiane Felícia dos Santos (2024)
Scorpion envenomation is responsible for a significant number of accidents, frequently surpassing those caused by all other venomous animals combined (Reckziegel & Pinto, 2004). In Brazil, it is classified as the second most common cause of human envenomation, second only to drug poisoning (Brasil, 2021). The species Tityus serrulatus is responsible for the majority of severe and sometimes fatal cases, particularly in children, due to the high toxicity of its venom. The objective of this study was to evaluate the possible association between baseline glycemic levels at admission and morbidity in children who were victims of scorpionism and treated at a reference toxicology service in Minas Gerais. This was a longitudinal, observational, and exploratory study with a quantitative approach, conducted between September 2023 and March 2024, including patients admitted to Hospital João XXIII of the Hospital Foundation of the State of Minas Gerais (FHEMIG). Glycemia measurements were taken at admission and two hours after serum therapy or observation. All analyses were performed using SPSS software version 23, with a significance level of 0.05, indicating that a p-value of <0.05 for a given variable showed a significant association. The study included 67children with an average age of 7.88 (±5.18) years. All cases classified as severe (13.4%) presented hyperglycemia at admission, and a significant reduction in glycemia levels was observed two hours after serum administration (p=0.008). The optimal cutoff value for glycemia was 142 mg/dL (p<0.001). Hyperglycemia did not occur in children classified as mild cases, and there was no significant reduction in measurements two hours after observation without serum therapy (p=0.335). The accuracy of the morbidity score created was significant (p<0.001), with a value of 0.924, indicating that 92.4% (95% CI: 0.779 – 1.000) of the classifications of cases as severe or not were correctly made using the score as a marker. Glycemia at admission proved to be an important biomarker of morbidity. A severity assessment score for scorpionism cases was developed, showing adequate diagnostic quality indices. The observed correlation between admission glycemia and the morbidity score for numerical values was considered positive.